Transcription factor defects in inborn errors of immunity with atopy - Vaseghi-Shanjani, Maryam; Yousefi, Pariya; Sharma, Mehul; Samra, Simran; Sifuentes, Erika; Turvey, Stuart E.; Biggs, Catherine M. (Frontiers in Allergy, 2023)
Transcription factors (TFs) are critical components involved in regulating immune system development, maintenance, and function. Monogenic defects in certain TFs can therefore give rise to inborn errors of immunity (IEIs) with profound clinical implications ranging from infections, malignancy, and in some cases severe allergic inflammation. This review examines TF defects underlying IEIs with severe atopy as a defining clinical phenotype, including STAT3 loss-of-function, STAT6 gain-of-function, FOXP3 deficiency, and T-bet deficiency. These disorders offer valuable insights into the pathophysiology of allergic inflammation, expanding our understanding of both rare monogenic and common polygenic allergic diseases. Advances in genetic testing will likely uncover new IEIs associated with atopy, enriching our understanding of molecular pathways involved in allergic inflammation. Identification of monogenic disorders profoundly influences patient prognosis, treatment planning, and genetic counseling. Hence, the consideration of IEIs is essential for patients with severe, early-onset atopy. This review highlights the need for continued investigation into TF defects to enhance our understanding and management of allergic diseases.